2021
DOI: 10.1111/hex.13288
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of diagnosis, treatment and risk of late effects in Chinese survivors of childhood cancer in Hong Kong

Abstract: Background For survivors of childhood cancer, awareness of personal health risks is a critical component of long‐term health management. Objective To evaluate the awareness of the diagnosis, treatment and risk of late effects among survivors of childhood cancer in Hong Kong. Methods Between June 2019 and March 2020, this cross‐sectional study recruited 155 adult survivors (mean age = 26.9, standard deviation [SD] = 6.4 years) and 45 parents of paediatric survivors (mean age = 11.1, SD = 3.6 years) from a long‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…A set of educational materials was developed to provide information on CM theories and advice on CM use during the post-treatment phase. The materials was integrated as a part of the survivorship care plan, which currently contains personalized information on survivors' cancer diagnosis and treatment history, as well as late effects and health promotion advice adapted from the Children Oncology Group ( 20 , 21 ). The key information was focused on CM dietary therapies, herbal products, and non-oral approaches such as traditional exercises, and were developed based on clinical consensus and existing recommendations in the literature ( 9 , 10 ).…”
Section: Methodsmentioning
confidence: 99%
“…A set of educational materials was developed to provide information on CM theories and advice on CM use during the post-treatment phase. The materials was integrated as a part of the survivorship care plan, which currently contains personalized information on survivors' cancer diagnosis and treatment history, as well as late effects and health promotion advice adapted from the Children Oncology Group ( 20 , 21 ). The key information was focused on CM dietary therapies, herbal products, and non-oral approaches such as traditional exercises, and were developed based on clinical consensus and existing recommendations in the literature ( 9 , 10 ).…”
Section: Methodsmentioning
confidence: 99%
“…The primary outcome was pre‐intervention to postintervention change in the participants’ cancer‐specific health literacy. The approach used to assess cancer‐specific health literacy was adapted from landmark studies 15–17 ; the details and a sample of the assessment tool were reported in our previous study 13 . Briefly, the approach assesses survivors’ knowledge of their cancer diagnosis and risk‐based, exposure‐related LEs.…”
Section: Methodsmentioning
confidence: 99%
“…They also review such information periodically with long‐term survivors when they visit the long‐term follow‐up (LTFU) clinic yearly. However, we previously reported that these survivors demonstrated deficient knowledge of treatment‐related LEs, with less than half (45%) of the surveyed survivors or caregivers recognizing more than 25% of the total LEs for which they were at risk 13 . The provision of personalized education and an SCP as part of a comprehensive survivorship program for this special population may improve their awareness of personal health risks.…”
Section: Introductionmentioning
confidence: 99%
“…We used domains derived from the Cancer Survivorship Care Quality Framework 12 as a guide to search and select literature (detailed in Appendix S1 , S2 ) and synthesize findings from Chinese childhood cancer survivor populations. Below we presented highlights from studies published between January 1, 2000 and June 30, 2021 in English 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 or Chinese language 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 (Table 1 , Appendix S3 ) to shed light on the gaps in previous literature and opportunities for future research.…”
Section: Domains Of Cancer Survivorshipmentioning
confidence: 99%
“…This study also found that chronic conditions developed after the cancer treatments were associated with multiple measures of behavior problems, such as executive dysfunction and attention problems. 26 Although long‐term and late effects of cancer treatment are common among childhood cancer survivors, another study in Hong Kong found that, among 200 survivors at least 10 years post‐treatment, most were not able to accurately identify the late effects that they were at risk for, 27 suggesting that improvements in health literacy of late effects are warranted among childhood cancer survivors.…”
Section: Research Addressing Physical Late Effects Of Cancer Treatmentmentioning
confidence: 99%